2017
DOI: 10.5114/fmpcr.2017.69285
|View full text |Cite
|
Sign up to set email alerts
|

Learned helplessness and its associations with illness perception, depression and anxiety among patients with systemic lupus erythematosus

Abstract: Background. Systemic lupus erythematosus (Sle) is a chronic, multi-organ disease that significantly impacts patients' psychological functioning. learned helplessness (lH) and illness perception have been proven to influence patients' emotional and physical state and treatment adherence. Objectives. the study is aimed at exploring learned helplessness and its relationship with illness perception, depression and anxiety among patients with Sle. Material and methods. the participants were 59 outpatients diagnosed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…Our finding emphasized the role of anxiety, which, according to the literature review, was a mostly ignored phenomenon in studies on SLE 39,40 despite the fact that anxiety symptoms seem to be more severe than depression in SLE sufferers and coexist with suicidal ideation. 11,41,42 Consistent with other authors, we suggest that many patients may not meet the diagnostic criteria of a particular anxiety disorder; 39 however, they may suffer from an increased level of anxiety and routine assessment of anxiety in patients with SLE seems vital. 8,39,40…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our finding emphasized the role of anxiety, which, according to the literature review, was a mostly ignored phenomenon in studies on SLE 39,40 despite the fact that anxiety symptoms seem to be more severe than depression in SLE sufferers and coexist with suicidal ideation. 11,41,42 Consistent with other authors, we suggest that many patients may not meet the diagnostic criteria of a particular anxiety disorder; 39 however, they may suffer from an increased level of anxiety and routine assessment of anxiety in patients with SLE seems vital. 8,39,40…”
Section: Discussionsupporting
confidence: 86%
“…[7][8][9][10] Qualitative studies revealed that illness perception in patients suffering from SLE is very individualized and heterogeneous. [4][5][6] Quantitative analyses provided evidence for connections between illness perception dimensions and psychological 8,11 as well as physical functioning 12 among patients with SLE. Illness perception can also be a significant co-factor influencing treatment adherence in patients with lupus nephritis.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the present study are comparable to previous reports that revealed that a more negative perception of illness is associated with higher anxiety ( 39 ). Similarly, an association of helplessness with anxiety and depression was reported in patients with systemic lupus erythematosus ( 40 ). In a study conducted among patients with type 1 diabetes, those who perceived disease benefits had more positive illness perception and lower levels of depression, anxiety, and irritability ( 41 ).…”
Section: Discussionmentioning
confidence: 65%
“…On the contrary, when parents treat the child with a chronic illness without honestly communicating about the medical condition, and as if they are in a weak and dependent situation, the child could be socialized toward a sense of learned helplessness. This perception of helplessness because of the illness could influence the patient’s emotional or physical state and treatment adherence (Nowicka-Sauer et al, 2017 ). Learned helplessness is defined, as the feeling that there is little control over their illness and subsequent experience, sensing no hope in fighting the symptoms of the illness, and resulting in a passive coping style.…”
Section: Socialization Influences: Parenting a Child With Chronic Ill...mentioning
confidence: 99%
“…Learned helplessness is defined, as the feeling that there is little control over their illness and subsequent experience, sensing no hope in fighting the symptoms of the illness, and resulting in a passive coping style. Psychosocial intervention such as patient empowerment and modification of negative perception of self is essential to reduce maladaptive psychological functioning (Nowicka-Sauer et al, 2017 ).…”
Section: Socialization Influences: Parenting a Child With Chronic Ill...mentioning
confidence: 99%